1998
DOI: 10.1007/s004670050517
|View full text |Cite
|
Sign up to set email alerts
|

Progression to end-stage renal disease in children with posterior urethral valves

Abstract: Diagnostic and therapeutic strategies in boys with congenital posterior urethral valves (PUV) have much improved in past decades, but the impact of these changes on the progression to end-stage renal disease (ESRD) has rarely been investigated. We followed renal function in 20 boys with PUV from diagnosis to ESRD. From the first observation period (1969-1978) to the second period (1979-1992) we found a marked drop in age at diagnosis, at valve resection, at first increase of serum creatinine (SCr), and at onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
2
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 34 publications
5
34
2
1
Order By: Relevance
“…Previous reports have consistently identified a number of other clinical characteristics associated with a poor outcome in these boys, including delayed diagnosis and surgical intervention [36,37], the presence of high-grade VUR [10,14], impaired kidney function when evaluated postnatally at various times [12,38], and an elevated nadir serum creatinine [39]. We also found that upper tract diversion was associated with a poor outcome.…”
Section: Discussionsupporting
confidence: 61%
“…Previous reports have consistently identified a number of other clinical characteristics associated with a poor outcome in these boys, including delayed diagnosis and surgical intervention [36,37], the presence of high-grade VUR [10,14], impaired kidney function when evaluated postnatally at various times [12,38], and an elevated nadir serum creatinine [39]. We also found that upper tract diversion was associated with a poor outcome.…”
Section: Discussionsupporting
confidence: 61%
“…There are conflicting evidence about the prognostic value of sCr before and after bladder catheterization. Some suggested more accurate prognostic value of sCr at 1 year after decompression than the initial values (14). However, sCr before bladder catheterization was significatly associated with ESRD, rather than after bladder decompression in our study (3).…”
contrasting
confidence: 56%
“…(d) sCr after valve ablation has a high prognostic value for prediction of final renal outcome (5). sCr values after urinary catheterization was higher in males who developed decreased renal function than those who did not (7). Creatinine velocity as the rate of sCr following initial bladder drainage is a recently introduced predictor of CKD in neonates with PUV (13).…”
mentioning
confidence: 99%
“…With α-tocopherol supplementation, the MDA content decreased to 88.0±5.7 µM (P=0.28). Figure 4 shows that the TGFβ1 mRNA, normalized to cyclophilin, was elevated (0.98±0.04 ADU) in the ate surgical procedure to relieve ureteral obstruction, performed shortly after birth, has made no significant difference in elapsed time from diagnosis to dialysis and renal transplantation [22][23][24][25][26]. Intrauterine surgical correction of this condition is difficult and costly.…”
Section: Resultsmentioning
confidence: 99%